The Learning Assistance for Students in Solving HOTS Type Questions on Polynomial Material - Nursalam,; Muhammad Nur Ihsan Hamin,; Lisa Kurnia Syam,; Aminullah,; Musdalifah, (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2024)
The ability to think at a higher level, involving analysis, evaluation, and creation, is a stage of higher-order thinking skills (HOTS). The implementation of the curriculum emphasizes the development of HOTS thinking skills. Some of the obstacles found include the ability of students to solve problems with the HOTS type, including polynomial material. Some students have difficulty conceptually implementing polynomials with analysis and criticism in solving problems that require a higher level of thinking. The service carried out was in the form of assistance to students in class XI Package 8 MAN 2 Makassar City, which aimed to improve students' ability to solve HOTS questions on polynomial material. The service was carried out with an interactive approach and based on practical exercises related to HOTS questions. Evaluation of service success rate is carried out through a learning outcome test that includes HOTS questions and student response questionnaires. Based on the analysis of the learning outcome test, it was obtained that the average score of students was 78.8 with a medium category. The study of student responses obtained a response percentage of 80.53 with a positive category. The results of this evaluation show that practical and effective practice-based mentoring improves students' HOTS abilities in polynomial materials. Thus, service activities in the form of assistance in solving HOTS questions are feasible to be carried out on an ongoing basis to improve students' HOTS abilities.